Neighbouring Group Participation in Micellar Catalysed Hydrolysis of Schiff Bases - Sankaran, K.R.; Lakshmi, R.L. (Asian Journal of Chemistry, 2010)
The rate of alkaline hydrolysis of Schiff bases in 30% aq.acetonitrile exhibits second order kinetics-first order in each reactant.The presence of neighbouring hydroxyl group in the benzaldehydeportion enhances the rate of hydrolysis, probably due tostabilisation 'of transition state. Such a neighbouring group effectseems to be most pronounced in anionic micelles of NaLS than incationic micelles of CTAB. The greater Hammet negative reactionconstant, P, in NaLS medium (-0.96) than in CTAB (p = -0.59) issuggestive of greater electronic influence of substituents on the rateof hydrolysis in NaLS than in CTAB.